A Lightweight Verification Method Based on Metamorphic Relation for Nuclear Power Software - Li, Meng; Yang, Xiaohua; Yan, Shiyu; Liu, Jie; Liu, Yusheng; Sun, Jun (Frontiers in Energy Research, 2022)
The verification of nuclear design software commonly uses direct comparison methods. Benchmark questions, classical programs, experimental data, manual solutions, etc., would be used as expected results to compare with program outputs to evaluate the reliability of software coding and the accuracy of the numerical solution. Because nuclear power software numerically simulates complex physical processes, it involves many partial differential equations. It is usually challenging to construct analytical or accurate solutions and is expensive to develop benchmark questions and experimental data. Hence, the quantity of verification examples is small. By using the direct comparison method, verification is complicated, high cost, and inadequate. Entering the validation process without adequate verification will adversely impact the effectiveness and efficiency of validation. Metamorphic testing is an indirect verification technology that cleverly combines the nature of the model with software verification. It evaluates the correctness of the code by examining whether the program satisfies the metamorphic relation. Without manual solutions or benchmark examples, it has broad application prospects in the field of nuclear power. A lightweight verification method based on metamorphic relation has been produced here. Metamorphic relations are identified from physical equations, numerical algorithms, and program specifications. Next, they are explicitly used to system, integration, and unit tests to improve test adequacy. Because no need to develop verification examples, this method can detect program errors as soon as possible at a low cost, improve test efficiency, avoid mistakes remain in subsequent stages and reduce the overall cost of verification.